Fire strike ebook - Maden, Mike (Oregon Files, 2023)
Juan Cabrillo and the crew of the Oregon must battle an army of genetically engineered mercenaries to stop a hypersonic missile attack in this explosive new adventure in the #1 New York Times bestselling series.     When Cabrillo is hired to extract an undercover operative in Kenya, he finds himself on the trail of a deadly international plot. A Saudi prince seeks to unleash a deadly assault on U.S. forces, sparking a new war in the Middle East and ultimately destroying Israel.     Cabrillo’s crew have met their most fearsome adversaries yet: a force of bio-hacked soldiers endowed with extreme strength and stamina and an unquenchable appetite for violence. The Oregon team must journey from the Amazon rainforest to an abandoned monastery in Eritrea before a final showdown in the mountains of Yemen, using every shred of courage and cunning they can muster to disable the ship-killer missile before the Arabian Sea becomes a mass grave.